THE MANAGERIAL CONCEPTS OF THE QUALITY AND PERFORMANCE AND THEIR INTEGRATION IN THE SPORTS ORGANIZATIONS - Jana Nová (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: This paper explores the possibilities of interconnection between the concepts of quality management systems and the concepts of the performance in sports organizations so to achieve the greater effectiveness and efficiency in terms of their operations. Therefore the paper provides an overview of the quality management systems and principles which are applicable in sports organizations and special attention is also paid to the analysis of the Balanced Scorecard principles in the sport context. Via the chosen methodology the author analyses the potential of this performance measurement tool for the integration into quality management system in sports organizations. Methods: In the paper the author used different methods of scientific research namely systematic observation, desk research, descriptive and causal method as well as the inductive and deductive method. The methods of analysis and synthesis of the existing perspectives were exploited in order to analyse and describe the interrelatedness between the different concepts. Results: The profound analysis and synthesis of the existing theoretical and practical tools applied in the quality of sport and performance of sport has proved the rightfulness of the assumptions that these two concepts can be based on their logic integrated in the managerial practice in one framework. Discussion: Implementing the integrated concept of the quality management and performance management in the sport organizations can be very efficient, considering the characteristics of the quality management systems and performance measurement. This approach can improve the realisation and results of the core processes in sport organizations and enhance their accountability towards the stakeholders´ requirements and expectations. References: Hoye R at al. (2012). Sport Management - principles and applications. Third edition. Routledge NY. Kaplan RE, Norton DP (1992). Harvard Business Review, 71-9. Nová J (2013). Current Concepts of the Quality in Sport and Their Possible Utilization in the Czech Republic. In: Conference Proceedings Prague, November 2013.Economics, Management and Marketing of Sport 2013, International Conference.